Potensi Pigmen Cassiavera pada Minuman Jahe Instan Sebagai Minuman Fungsional - Firdausni, Firdausni; Failisnur, Failisnur; Diza, Yulia Helmi (Jurnal Litbang Industri, 2011)
Cassiavera (Cinnamomum burmannii) contains reddish brown to dark brown pigment that can be used as additives in instant ginger drink. The pigment was generated by maceration method in water at initial temperature 25-27ºC and 85-100ºC with maceration time of 24, 48 and 72 hours. Cassiavera filtrate with optimal color intensity was then added to the ginger powder in the ratio w/v (10:1), (10:2) and (10:3). The potency of cassiavera pigment in the instant ginger was seen from the color intensity by using a spectrophotometer, test of total phenols and panelist preference level of aroma, color, and flavor generated. Results of the research showed that the treatment time of maceration significantly affected the color intensity of the product. The best treatment of cassiavera pigment generating was found on maceration with water at temperature 85-100ºC for 48 hours and comparison of ginger powder and cassiavera filtrate 10:3 (w/v) with the highest color intensity 0, 3813 and the color preferred by the panelists. Total phenol was 26.51 ppm, with average values of organoleptic test of taste, color, and aroma were 3.20, 3.40, and 3.40 respectively. The Color intensity was measured by using a spectrophotometer at a wavelength of 556 nm indicated the intensity of color between 0.0345 - 0.3813, and total phenols between 20.47 and 26.51 ppm.ABSTRAKCassiavera (Cinnamomum burmannii) mengandung pigmen berwarna coklat kemerahan sampai coklat tua yang digunakan sebagai bahan tambahan pada minuman jahe instan. Pengambilan pigmen dengan maserasi air pada suhu awal 25-27ºC dan 85-100ºC dengan lama maserasi 24, 48 dan 72 jam. Filtrat cassiavera dengan intensitas warna optimal yang didapatkan selanjutnya ditambahkan pada jahe bubuk dengan perbandingan antara jahe bubuk dan filtrat cassiavera b/v (10:1), (10:2) dan (10:3). Potensi pigmen cassiavera pada jahe instan dilihat dari intensitas warna dengan menggunakan spektrofotometer, uji total fenol dan tingkat kesukaan fanelis terhadap aroma, warna, dan rasa yang dihasilkan. Hasil penelitian menunjukkan bahwa perlakuan lamanya maserasi berpengaruh nyata terhadap intensitas warna produk. Pada pengambilan pigmen cassiavera didapatkan perlakuan terbaik pada  maserasi dengan air pada suhu 85-100ºC selama 48 jam dan perbandingan jahe bubuk dengan filtrat cassiavera dalam pembuatan jahe cassiavera instan adalah 10:3 (b/v) dengan intensitas warna tertinggi 0,3813, memiliki total fenol 26,51 ppm, aroma, warna, dan rasa yang disukai oleh panelis  dengan nilai rata rata  3,40; 3,47, dan  3,20. Pengujian intensitas warna menggunakan spektrofotometer yang diukur pada panjang gelombang 556 nm menunjukkan intensitas warna antara 0.0345-0.3813, dan total fenol antara 20,47-26,51 ppm.